« Can't repeat the past? Well maybe not... » A Doomed Trip Down Memory Lane, in Francis Scott Fitzgerald's Southern Stories - Pascal Bardet (Les Cahiers de Framespa, 2017)
Scott Fitzgerald is not a Southern writer, but this US region holds a significant place in his fiction. Indeed, more than being a mere backdrop in his novels, the South appears as a central setting in some of Fitzgerald’s shorter fiction. The fictional town of Tarleton is found in four short-stories: «The Ice Palace», «The Jelly-Bean», «Dice, Brass Knuckles and Guitar» and «The Last of the Belles». In each story, the American South is never analyzed or described per se but always in comparison to northern places that put each character to the test and make them long for the land of their lost youth and innocence. The South, the archetypal land of pastoral traditions and romantic elation, becomes nothing more than a lost paradise where the past cannot repeat itself and where the trip down memory lane is ineluctably doomed.